(untitled) (Revista Argentina de Musicología, 2018)
The textural stratification in the music of Charles E. Ives hinges on a marked individuation of the elements that make up the texture. Such individuation results from the materials being elaborated with independence of the totality they conform, but no longer governs them. Textura! stratification can thus be understood as an immanent criticism to the binding character of tonality, to its status as a regulatory element of music in general and as a foundation for the logic of simultaneity in particular. A combination of elements such as heterogeneity and individuation of materials, stratification associated with a disintegrated simultaneity, and the treatment of tonality as a dehistorized material are noticeable in The Unanswered Question, a work Ives composed between 1906 and 1930/35.